Changing Your Lifestyle to Change the World. Who Is Willing to Take up the Challenge of the Globalisation of Risks? - Di Nicola, Paola (Italian Sociological Review, 2017)
This article aims to analyse the degree to which a sample of the Italian population has assimilated a new form of awareness of consumption. The focus is not on concrete behaviour, but on the willingness to ‘renounce something’ – in terms of consumer goods – for a general interest. It cannot be assumed that all consumers have the same level of sensitivity to the issues raised by environmentalists, the fair trade movement or degrowth; some of the discriminating variables that can influence the relative willingness of consumers to modify aspects of their behaviour include generalised trust, political culture of belonging, local traditions and perception of the degree of influence that individual action can have on the political context, together with the more traditional profile variables such as gender, age, level of education, area of residence and social class. It is assumed that a greater or lesser willingness to change lifestyle cannot be separated from the broader social context in which consumers act, as our daily lives are marked by frequent purchases that are often routine, but also subject to systematic assessments in terms of price, value for money, beauty, self-gratification and symbolic and material investments.